2022
DOI: 10.3389/fbioe.2022.918126
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-assisted alkaline pretreatment and enzymatic hydrolysis of Miscanthus sinensis for enhancing sugar recovery with a reduced enzyme loading

Abstract: Surfactants play a vital role in the delignification and saccharification of lignocellulosic biomass. A strategy for coupling surfactant-assisted alkaline pretreatment (SAP) with surfactant-assisted enzymatic hydrolysis (SEH) has been proposed for improving sugar recovery from a potential energy crop, Miscanthus sinensis. Poly (ethylene glycol) 2000 (PEG 2000) was found to be more efficient in SAP than in other tested surfactants. Compositional and structural analysis revealed that the SAP process with 1% of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Additionally, it is plausible that the treatment dissolves hemicelluloses associated with or covering lignin, thereby augmenting cellulase accessibility and subsequent cellulose adsorption. Extending the treatment duration may further enhance accessibility, consequently increasing the expected glucose yield (Ghavi et al 2021;Cheng et al 2022). However, further research is imperative to establish a definitive correlation between surfactant effects and substrate characteristics.…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, it is plausible that the treatment dissolves hemicelluloses associated with or covering lignin, thereby augmenting cellulase accessibility and subsequent cellulose adsorption. Extending the treatment duration may further enhance accessibility, consequently increasing the expected glucose yield (Ghavi et al 2021;Cheng et al 2022). However, further research is imperative to establish a definitive correlation between surfactant effects and substrate characteristics.…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%
“…Surfactants play a vital role in the pretreatment and enzymatic hydrolysis of lignocellulosic biomass. They can help to enhance the delignification and saccharification of the biomass, thereby improving the yield of reducing sugars (Cheng et al 2022). According to the experiment done by Cheng et al a strategy for coupling surfactantassisted alkaline pretreatment with surfactant-assisted enzymatic hydrolysis has been proposed for improving sugar recovery from lignocellulosic biomass and results showed that the surfactant-assisted alkaline pretreatment process with 1% of PEG 2000 resulted in more efficient lignin removal and microstructure disruption of the pretreated sample, thus indicating much higher reducing sugar yields.…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%
See 2 more Smart Citations
“…The quantum yield (QY) was measured by Fluorescence (F-7100) and UV-visible spectrophotometer (UV-2700), and the data of QY was calculated according to Eq. ( 4) (Li X X et al, 2022):…”
Section: Chemical Composition Analysismentioning
confidence: 99%